Intermediate carbene formation in the reaction of thioamides with phosphorus (III) derivatives: Quantum chemical investigation. Issue 4 (8th October 2013) - Rozhenko, Alexander B.; Mykhaylychenko, Sergiy S.; Pikun, Nadiya V.; Shermolovich, Yuriy G.; Leszczynski, Jerzy
<x xml:space="preserve">Abstract</x> The reactions of perfluoroalkyl thioamides with trimethyl phosphine, trimethyl phosphite, and tris(dimethylamino)phosphine have been analyzed by means of quantum chemical (DFT and MP2) calculations. The reaction seems to proceed via the nucleophilic attack of the electrophilic carbon atom by the phosphorus lone pair with the formation of cyclic or acyclic adducts. The latter releases the thiophosphate molecule forming perfluoroalkylaminocarbene as the short‐lived intermediate. The reaction of the carbene with the second molecule of trialkyl phosphite yields phosphorus ylide. The ylide undergoes a migration of fluorine from carbon to phosphorus. The reactions of perfluoroalkyl thioamides with phosphines and tris(dimethylamino)phosphine probably proceeds differently. Using alkyl thioamides or amides instead of perfluoroalkyl thioamides also makes the reaction less favorable. The only combination of perfluoroalkyl thioamides with trialkyl phosphite fulfills both the kinetic requirements (moderate activation energies and relative energies for intermediates) and the thermodynamic aspects (higher stabilities of the reaction products compared with the starting materials). © 2013 Wiley Periodicals, Inc.